In4Sn3O12 target material and preparation method thereof

Through co-precipitation method and organic acid activation technology, high density and low resistivity In4Sn3O12 targets were prepared, which solved the problem of insufficient density and resistivity of the target in the prior art, and achieved process simplification and reduction of production costs.

CN119430864AActive Publication Date: 2025-02-14ZHONGSHAN ZL ADVANCED MATERIALS TECHNOLOGY
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
CN202411492712.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-14
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

In the prior art, the density and resistivity of the In4Sn3O12 target material are insufficient, and the process is complex, resulting in low production efficiency and high cost.

Method used

In4Sn3O12 powder was prepared by co-precipitation method, the powder was activated by organic acid, the sintering temperature was reduced, and the mold molding and sintering process optimization was used to obtain high density and low resistivity In4Sn3O12 target materials.

Benefits of technology

The density of In4Sn3O12 target material is achieved ≥99.2% and the resistivity is ≤8×10-4Ω·cm, and the process flow is simplified, production costs are reduced, and uniformity is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100497400000111
    Figure BDA0005100497400000111
  • Figure BDA0005100497400000121
    Figure BDA0005100497400000121
  • Figure BDA0005100497400000122
    Figure BDA0005100497400000122
Patent Text Reader

Abstract

The invention provides an In4Sn3O12 target material and a preparation method of the In4Sn3O12 target material. The density of the target material is greater than or equal to 99.2%, the resistivity is less than or equal to 8 * 10 <-4 > omega.cm, and the target material has high uniformity. The invention also provides a preparation method of the In4Sn3O12 target material, which comprises the following steps of: dissolving metal indium and metal tin serving as raw materials with acid to obtain a mixed metal salt solution, dripping the mixed metal salt solution into ammonia water, precipitating to form indium hydroxide and tin hydroxide precipitates, and drying to obtain the In4Sn3O12 target material. The preparation method comprises the following steps: preparing indium hydroxide and tin hydroxide precipitates, drying the indium hydroxide and tin hydroxide precipitates to obtain mixed powder, heating and reacting to obtain In4Sn3O12 powder, activating and granulating the In4Sn3O12 powder through organic acid to obtain granulated powder, forming the granulated powder through a mold to obtain a biscuit, and sintering the biscuit to obtain the In4Sn3O12 target material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of low indium target material preparation, and specifically relates to an In 4 Sn 3 O 12 Target material and preparation method thereof. Background Art

[0002] Transparent Conductive Oxide (TCO film for short) is a key material in devices such as displays, heterojunction solar cells, Low-E glass, and electrochromic devices. Indium Tin Oxide (ITO) targets are the main raw materials for the industrial preparation of TCO films. The mass fraction of indium oxide in commonly used ITO targets is greater than or equal to 90% (i.e., 90 / 10 ITO targets), corresponding to an indium content of 74.4% and above. Due to the high price and shortage of indium resources, the cost of ITO targets remains high, which limits its large-scale application and promotion in photovoltaics and Low-E glass. Therefore, there is an urgent need for a low-cost target with excellent optoelectronic properties.

[0003] In 4 Sn 3 O 12 The indium content is only 45.6%, which is a low-indium material that has attracted much attention and has great potential. 4 Sn 3 O 12 A low indium target material with an indium content of 43.5-55.7%. CN118084480A discloses an In 4 Sn 3 O 12 These technologies have some shortcomings. Specifically, the low indium target prepared by CN116496081 A has a relative density of ≥98% and a resistivity of ≤5×10 -3 Ω·cm, but the relative density of 90 / 10ITO targets used on a large scale in industry is mostly ≥99%, and the resistivity is ≤1×10 -3 Ω·cm, so it is necessary to further improve In 4 Sn 3 O 12The density of the target material is increased and the resistivity is reduced. Although the density of the low-indium target material prepared by CN 118084480A is ≥99.5%, in order to remove the sintering aid antimony trioxide, the target material needs to be kept at a low temperature (1280-1320°C) for 20-40 hours during sintering to avoid antimony trioxide remaining as an impurity in the target material. This process reduces the sintering efficiency of the target material and increases the sintering cost. On the other hand, the above-mentioned technologies all use indium oxide and tin oxide as raw materials and adopt a solid phase reaction to directly synthesize In 4 Sn 3 O 12 However, the uniformity of solid phase synthesis is relatively poor. CN116496081A improves its uniformity by pre-sintering and secondary ball milling mixing, but this makes the process more complicated and reduces production efficiency.

[0004] Therefore, it is necessary to develop a new In 4 Sn 3 O 12 Method for preparing target material. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides an In 4 Sn 3 O 12 The target material preparation method is to prepare In by coprecipitation method. 4 Sn 3 O 12 Powder, simplifies the preparation process and improves the uniformity of indium tin mixing. Organic acid is used to activate In 4 Sn 3 O 12 Powder, reduce the sintering temperature, and finally obtain density ≥99.2% and resistivity ≤8×10 -4 Ω·cm, and high uniformity of In 4 Sn 3 O 12 base target material.

[0006] A first aspect of the present invention provides an In 4 Sn 3 O 12 The method for preparing a target material comprises the following steps:

[0007] S1: using metal indium and metal tin as raw materials, dissolving them by acid to obtain a mixed metal salt solution, dropping the mixed metal salt solution into ammonia water to precipitate indium hydroxide and tin hydroxide precipitates, drying the indium hydroxide and tin hydroxide precipitates to obtain a mixed powder and heating the mixture to obtain In 4 Sn 3 O 12Powder, the In 4 Sn 3 O 12 Granulating the powder to obtain granulated powder;

[0008] S2: forming the granulated powder through a mold to obtain a green blank;

[0009] S3: Sinter the green blank to obtain In 4 Sn 3 O 12 Target material.

[0010] The present invention relates to 4 Sn 3 O 12 A technical solution in the method for preparing a target material has at least the following beneficial effects:

[0011] The present invention adopts the coprecipitation method to first prepare In 4 Sn 3 O 12 Powder, simplifies the preparation process and improves the uniformity of indium tin mixing. Organic acid is used to activate In 4 Sn 3 O 12 Powder, reduce the sintering temperature, and finally obtain density ≥99.2% and resistivity ≤8×10 -4 Ω·cm, and high uniformity of In 4 Sn 3 O 12 base target material.

[0012] Although coprecipitation is a conventional powder making process and is widely used in various fields, many powders can be prepared by coprecipitation. However, due to the different material systems, the coprecipitation in the present invention is different from the existing coprecipitation process and mechanism. In the present invention, high uniformity can be achieved by acid dissolving metal indium and metal tin, while simplifying the process flow. The difficulty of the present invention lies in the order of the mixed solution during coprecipitation (In(OH) 3 and Sn(OH) 4 K sp Different), K sp That is, the ion equilibrium constant of the insoluble substance (precipitate), also known as the solubility product, which is equal to the product of the concentrations of cations and anions. When the product exceeds K sp When the precipitate is formed, a precipitate is formed. For example, in the present invention, In(OH) 3 and Sn(OH) 4 They are all substances that are difficult to dissolve in water, appearing as precipitation, and there is a large amount of In in the solution. 3+ and Sn 4+ At this time, an alkaline solution is added to provide OH -, when OH - When the concentration exceeds a certain limit, In(OH) 3 and Sn(OH) 4 It should be noted that due to the K sp There is a difference. If you reverse the order of adding, 3+ and Sn 4+ Ammonia water (providing OH) is gradually added to the solution. - ), at this time, because the cation is in excess, and OH - The amount is small, so K sp Smaller hydroxides will precipitate first, resulting in uneven precipitation (the chemical composition of different particles is very different). That is, if ammonia water is gradually dripped into the mixed solution, even if corresponding dispersing and homogenizing measures are also taken at the same time, uneven precipitation will occur. In addition, sodium silicate is usually added as a dispersant during the preparation of nanopowders, but for TCO targets, silicon and sodium are seriously harmful impurities. The present invention drips the mixed metal salt solution into ammonia water, and the ammonia water is always kept in an excess state. The mixed metal salt solution is gradually dripped into the ammonia water, and the dripping speed is controlled, thereby ensuring that the dripped In 3+ and Sn 4+ The precipitation is almost complete at the same time, avoiding the problem of uneven precipitation, improving the uniformity of indium tin mixing, and activating In 4 Sn 3 O 12 The organic acid in the powder will volatilize during the high-temperature sintering process of the target material and will not introduce new impurities.

[0013] In addition, the present invention does not have a particularly high requirement for the powder particle size, thereby simplifying the preparation process. Since the requirement for the powder particle size is relatively low, the synthesized In 4 Sn 3 O 12 Powder sand grinding is sufficient, which only requires refining the powder through physical methods.

[0014] In the present invention, the prepared target main matrix is ​​In 4 Sn 3 O 12 , which is a hexagonal crystal, and is different from the Sn-doped In 2 O 3 A completely different system.

[0015] The preparation method of the present invention does not require expensive equipment and complicated process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, and is easy to industrialize.

[0016] According to some embodiments of the present invention, in step S1, the mass fraction of indium in the metallic indium and metallic tin raw materials is 39.5% to 56.8%.

[0017] In the metallic indium and metallic tin raw materials, the mass fraction of indium is 39.5% to 56.8%, which is low indium and greatly reduces the cost.

[0018] According to some embodiments of the present invention, in step S1, the acid includes concentrated nitric acid or concentrated hydrochloric acid.

[0019] According to some embodiments of the present invention, the concentration of the concentrated nitric acid is 50% to 65%.

[0020] A nitric acid solution is added according to 1.05-1.15 times the amount required to completely generate indium nitrate and tin nitrate to ensure that the metal indium and tin can be fully dissolved. After fully dissolving for 2-5 hours, a mixed metal salt solution is obtained.

[0021] According to some embodiments of the present invention, the concentration of the concentrated hydrochloric acid is 20% to 38%.

[0022] According to some embodiments of the present invention, in step S1, the concentration of the ammonia water is 20% to 28%.

[0023] According to some embodiments of the present invention, in step S1, the concentration of the ammonia water is any value of 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28% or a range formed by any two of them, such as 24% to 26%.

[0024] According to some embodiments of the present invention, the amount of ammonia water used is 1.08 to 1.20 times the amount required for all of the metal indium and metal tin to generate metal salts.

[0025] According to some embodiments of the present invention, the amount of ammonia water used is any value among 1.08, 1.12, 1.14, 1.16, 1.18, 1.20 times the amount of metallic indium and metallic tin required to generate metal salts, or a range formed by any two of them, such as 1.14 to 1.18 times.

[0026] According to some embodiments of the present invention, step S1 further includes adding 0.2wt% to 0.6wt% of polyvinyl pyrrolidone as an organic dispersant to the ammonia water to promote the complete reaction, and starting ultrasonic dispersion while forming indium hydroxide and tin hydroxide precipitates. After complete precipitation, the obtained indium hydroxide and tin hydroxide precipitates are centrifuged to remove acid ions, and then spray-dried to obtain a mixed powder.

[0027] According to some embodiments of the present invention, the number of centrifugal washing is 3 to 6 times.

[0028] According to some embodiments of the present invention, in step S1, ammonia water can be placed in a stirring tank, an organic dispersant (0.2wt% to 0.6wt% of polyvinyl pyrrolidone) can be added, and stirring and ultrasound can be turned on at the same time. The combined effect of the three can further improve the uniformity of precipitation.

[0029] According to some embodiments of the present invention, in step S1, the temperature-raising reaction process includes: keeping the temperature at 500°C to 600°C for 2h to 8h, keeping the temperature at 1000°C to 1200°C for 3h to 8h, and keeping the temperature at 1300°C to 1500°C for 1h to 5h. Keeping the temperature at multiple temperature intervals promotes a more thorough reaction.

[0030] According to some embodiments of the present invention, in step S1, the In 4 Sn 3 O 12 The process of powder activation and granulation by organic acid includes: 4 Sn 3 O 12 After the powder is ball-milled in a sand mill for 6h to 10h, powder D is obtained. 90 <100nm slurry, transfer the slurry to a stirrer, add organic acid to make the acid concentration in the slurry 0.3mol / L~1.2mol / L, and stir at a speed of 50rpm~120rpm for 2h~8h, then add binder and plasticizer to the slurry and stir, then spray granulate to obtain granulated powder.

[0031] According to some embodiments of the present invention, the binder includes 0.5-2.0 wt % of PVA.

[0032] According to some embodiments of the invention, the plasticizer comprises 0.2-1.0 wt % PEG.

[0033] According to some embodiments of the present invention, the time for stirring after adding the binder and the plasticizer may be 1 hour to 3 hours.

[0034] According to some embodiments of the present invention, the organic acid comprises at least one of oxalic acid, acetic acid, citric acid and tartaric acid.

[0035] On the one hand, organic weak acids will react with the surface of the powder, causing certain crystal faces to be corroded and damaged preferentially, destroying the crystal structure and thus reducing the sintering activation energy; on the other hand, the organic acid salts generated by the reaction decompose at low temperatures (<900°C) to form a glass phase. The combined effect of these two aspects reduces the sintering temperature.

[0036] According to some embodiments of the present invention, in step S2, the molding pressure of the mold is 100MPa-180MPa, and after demolding, cold isostatic pressing is performed at 150MPa-220MPa for 20min-60min to obtain a green blank.

[0037] According to some embodiments of the present invention, in step S3, the sintering process includes: heating the blank to 600°C~800°C at a rate of 0.5~2°C / min and keeping it warm for 2h~6h, then heating it to 1300°C~1450°C at a rate of 1~3°C / min, while introducing oxygen at a rate of 5L / min~30L / min, and keeping it warm for 1h~5h, after the insulation is completed, keeping it warm at 1150°C~1300°C for 5h~10h, and finally cooling it to room temperature at a rate of 1°C / min~5°C / min.

[0038] A second aspect of the present invention provides an In 4 Sn 3 O 12 The target material is prepared by the method described in the first aspect of the present invention.

[0039] The present invention relates to 4 Sn 3 O 12 One of the technical solutions of the target material has at least the following beneficial effects:

[0040] In the present invention 4 Sn 3 O 12 The target material has the characteristics of high density, low resistivity and high uniformity.

[0041] According to some embodiments of the present invention, the In 4 Sn 3 O 12 The density of the target material is ≥99.2%, and the resistivity is ≤8×10 -4 Ω·cm. High uniformity, as shown by the resistivity difference at different locations on the target surface <8.0%. DETAILED DESCRIPTION

[0042] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0043] In a first aspect, some embodiments of the present invention provide an In 4 Sn 3 O 12 The method for preparing a target material comprises the following steps:

[0044] S1: Using metal indium and metal tin as raw materials, dissolving them by acid to obtain a mixed metal salt solution, dropping the mixed metal salt solution into ammonia water to precipitate indium hydroxide and tin hydroxide precipitates, drying the indium hydroxide and tin hydroxide precipitates to obtain a mixed powder and heating the mixture to obtain In 4 Sn 3 O 12 Powder, In 4 Sn 3 O 12 Granulating the powder to obtain granulated powder;

[0045] S2: forming the granulated powder through a mold to obtain a green blank;

[0046] S3: Sintering the green billet to obtain In 4 Sn 3 O 12 Target material.

[0047] It can be understood that the present invention adopts the coprecipitation method to first prepare In 4 Sn 3 O 12 Powder, simplifies the preparation process and improves the uniformity of indium tin mixing. Organic acid is used to activate In 4 Sn 3 O 12 Powder, reduce the sintering temperature, and finally obtain density ≥ 99.2%, resistivity ≤ 8×10-4Ω·cm, and high uniformity In 4 Sn 3 O 12 base target material.

[0048] It should be noted that although coprecipitation is a conventional powder making process and is widely used in various fields, many powders can be prepared by coprecipitation. However, due to the different material systems, the coprecipitation in the present invention is different from the existing coprecipitation process and mechanism. In the present invention, high uniformity can be achieved by acid dissolving metal indium and metal tin, while simplifying the process flow. The difficulty of the present invention lies in the order of the mixed solution during coprecipitation (In(OH) 3 and Sn(OH) 4 K sp Different), K sp That is, the ion equilibrium constant of the insoluble substance (precipitate), also known as the solubility product, which is equal to the product of the concentrations of cations and anions. When the product exceeds K sp When the precipitate is formed, a precipitate is formed. For example, in the present invention, In(OH) 3 and Sn(OH) 4 They are all substances that are difficult to dissolve in water, appearing as precipitation, and there is a large amount of In in the solution. 3+ and Sn 4+At this time, an alkaline solution is added to provide OH - , when OH - When the concentration exceeds a certain limit, In(OH) 3 and Sn(OH) 4 precipitation.

[0049] It should also be noted that since the two K sp There is a difference. If you reverse the order of adding, 3+ and Sn 4+ Ammonia water (providing OH) is gradually added to the solution. - ), at this time, because the cation is in excess, and OH - The amount is small, so K sp Smaller hydroxides will precipitate first, resulting in uneven precipitation (the chemical composition of different particles is very different). That is, if ammonia water is gradually dripped into the mixed solution, even if corresponding dispersing and homogenizing measures are also taken at the same time, uneven precipitation will occur. In addition, sodium silicate is usually added as a dispersant during the preparation of nanopowders, but for TCO targets, silicon and sodium are seriously harmful impurities. The present invention drips the mixed metal salt solution into ammonia water, and the ammonia water is always kept in an excess state. The mixed metal salt solution is gradually dripped into the ammonia water, and the dripping speed is controlled, thereby ensuring that the dripped In 3+ and Sn 4+ The precipitation is almost complete at the same time, avoiding the problem of uneven precipitation, improving the uniformity of indium tin mixing, and activating In 4 Sn 3 O 12 The organic acid in the powder will volatilize during the high-temperature sintering process of the target material and will not introduce new impurities.

[0050] In addition, the present invention does not have a particularly high requirement for the powder particle size, thereby simplifying the preparation process. Since the requirement for the powder particle size is relatively low, the synthesized In 4 Sn 3 O 12 Powder sand grinding is sufficient, which only requires refining the powder through physical methods.

[0051] It should also be noted that in the present invention, the main matrix of the target material prepared is In 4 Sn 3 O 12 , which is a hexagonal crystal, and is different from the Sn-doped In 2 O 3 A completely different system.

[0052] The preparation method of the present invention does not require expensive equipment and complicated process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, and is easy to industrialize.

[0053] In combination with the first aspect, in some embodiments of the present invention, in step S1, the mass fraction of indium in the metal indium and metal tin raw materials is 39.5% to 56.8%.

[0054] In the metallic indium and metallic tin raw materials, the mass fraction of indium is 39.5% to 56.8%, which is low indium and greatly reduces the cost.

[0055] In combination with the first aspect, in some embodiments of the present invention, in step S1, the acid includes concentrated nitric acid or concentrated hydrochloric acid.

[0056] In combination with the first aspect, in some embodiments of the present invention, the concentration of concentrated nitric acid is 50% to 65%.

[0057] A nitric acid solution is added according to 1.05-1.15 times the amount required to completely generate indium nitrate and tin nitrate to ensure that the metal indium and tin can be fully dissolved. After fully dissolving for 2-5 hours, a mixed metal salt solution is obtained.

[0058] In combination with the first aspect, in some embodiments of the present invention, the concentration of concentrated hydrochloric acid is 20% to 38%.

[0059] In combination with the first aspect, in some embodiments of the present invention, in step S1, the concentration of the ammonia water is 20% to 28%.

[0060] In combination with the first aspect, in some embodiments of the present invention, in step S1, the concentration of ammonia water is any value of 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28% or a range formed by any two of them, such as 24% to 26%.

[0061] In combination with the first aspect, in some embodiments of the present invention, the amount of ammonia water used is 1.08 to 1.20 times the amount required to generate metal salts of metal indium and metal tin.

[0062] In combination with the first aspect, in some embodiments of the present invention, the amount of ammonia water used is any value among 1.08, 1.12, 1.14, 1.16, 1.18, 1.20 times the amount of metallic indium and metallic tin required to generate all metal salts, or a range formed by any two of them, such as 1.14 to 1.18 times.

[0063] In combination with the first aspect, in some embodiments of the present invention, step S1 also includes adding 0.2wt% to 0.6wt% of polyvinyl pyrrolidone as an organic dispersant to the ammonia water to promote the reaction to be complete, and starting ultrasonic dispersion while forming indium hydroxide and tin hydroxide precipitates. After complete precipitation, the obtained indium hydroxide and tin hydroxide precipitates are centrifuged to remove acid ions, and then spray-dried to obtain a mixed powder.

[0064] In combination with the first aspect, in some embodiments of the present invention, the number of centrifugal washings is 3 to 6 times.

[0065] In combination with the first aspect, in some embodiments of the present invention, in step S1, ammonia water can be placed in a stirring tank, an organic dispersant (0.2wt% to 0.6wt% of polyvinyl pyrrolidone) can be added, and stirring and ultrasound can be turned on at the same time. The combined effect of the three can further improve the uniformity of precipitation.

[0066] In combination with the first aspect, in some embodiments of the present invention, in step S1, the process of heating the reaction includes: keeping the temperature at 500°C to 600°C for 2h to 8h, keeping the temperature at 1000°C to 1200°C for 3h to 8h, and keeping the temperature at 1300°C to 1500°C for 1h to 5h. Keeping the temperature at multiple temperature intervals promotes a more thorough reaction.

[0067] In combination with the first aspect, in some embodiments of the present invention, in step S1, In 4 Sn 3 O 12 The process of powder activation and granulation by organic acid includes: 4 Sn 3 O 12 After the powder is ball-milled in a sand mill for 6h to 10h, powder D is obtained. 90 <100nm slurry, transfer the slurry to a stirrer, add organic acid to make the acid concentration in the slurry 0.3mol / L~1.2mol / L, and stir at a speed of 50rpm~120rpm for 2h~8h, then add binder and plasticizer to the slurry and stir, then spray granulate to obtain granulated powder.

[0068] In combination with the first aspect, in some embodiments of the present invention, the binder includes 0.5-2.0 wt % of PVA.

[0069] In combination with the first aspect, in some embodiments of the present invention, the plasticizer includes 0.2-1.0 wt % PEG.

[0070] In combination with the first aspect, in some embodiments of the present invention, the time for stirring after adding the binder and the plasticizer may be 1 hour to 3 hours.

[0071] In combination with the first aspect, in some embodiments of the present invention, the organic acid includes at least one of oxalic acid, acetic acid, citric acid, and tartaric acid.

[0072] On the one hand, organic weak acids will react with the surface of the powder, causing certain crystal faces to be corroded and damaged preferentially, destroying the crystal structure and thus reducing the sintering activation energy; on the other hand, the organic acid salts generated by the reaction decompose at low temperatures (<900°C) to form a glass phase. The combined effect of these two aspects reduces the sintering temperature.

[0073] In combination with the first aspect, in some embodiments of the present invention, in step S2, the molding pressure of the mold is 100MPa to 180MPa, and after demolding, cold isostatic pressing is performed at 150MPa to 220MPa for 20min to 60min to obtain a green blank.

[0074] In combination with the first aspect, in some embodiments of the present invention, in step S3, the sintering process includes: heating the green billet to 600℃~800℃ at a rate of 0.5~2℃ / min and keeping it warm for 2h~6h, then heating it to 1300℃~1450℃ at a rate of 1~3℃ / min, while introducing oxygen at a rate of 5L / min~30L / min, and keeping it warm for 1h~5h, after the insulation is completed, keeping it warm at 1150℃~1300℃ for 5h~10h, and finally cooling it to room temperature at a rate of 1℃ / min~5℃ / min.

[0075] In a second aspect, some embodiments of the present invention provide an In 4 Sn 3 O 12 The target material is prepared by the method according to the first aspect of the present invention.

[0076] In the present invention 4 Sn 3 O 12 The target material has the characteristics of high density, low resistivity and high uniformity.

[0077] In conjunction with the second aspect, in some embodiments of the present invention, In 4 Sn 3 O 12 The density of the target material is ≥99.2%, and the resistivity is ≤8×10 -4 Ω·cm. High uniformity, as shown by the resistivity difference at different locations on the target surface <8.0%.

[0078] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0079] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0080] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0081] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.

[0082] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0083] Example 1

[0084] Prepared an In 4 Sn 3 O 12 Target material, the specific method is:

[0085] S1: Using metal indium and metal tin as raw materials, dissolving them by acid to obtain a mixed metal salt solution, dropping the mixed metal salt solution into ammonia water to precipitate indium hydroxide and tin hydroxide precipitates, drying the indium hydroxide and tin hydroxide precipitates to obtain a mixed powder and heating the mixture to obtain In 4 Sn 3 O 12 Powder, In 4 Sn 3 O 12 The powder is activated and granulated by organic acid to obtain granulated powder;

[0086] S2: forming the granulated powder through a mold to obtain a green blank;

[0087] S3: Sintering the green billet to obtain In 4 Sn 3 O 12 Target material.

[0088] In step S1:

[0089] In the metallic indium and metallic tin raw materials, the mass fraction of indium is 39.5%, and the mass fraction of tin is 60.5%.

[0090] The acid is concentrated nitric acid, and the concentration of the concentrated nitric acid is 60%.

[0091] The concentration of ammonia water is 24%, and the amount of ammonia water used is 1.15 times the amount required for the metal indium and the metal tin to generate metal salts.

[0092] 0.4 wt % of polyvinyl pyrrolidone is added to the ammonia water to promote the complete reaction. Ultrasonic dispersion is started while indium hydroxide and tin hydroxide precipitates are formed. After complete precipitation, the obtained indium hydroxide and tin hydroxide precipitates are centrifugally cleaned and then spray-dried to obtain a mixed powder.

[0093] The temperature reaction process includes: keeping at 550℃ for 4h, keeping at 1100℃ for 5h, and keeping at 1400℃ for 3h. 4 Sn 3 O 12 The process of powder activation and granulation by organic acid includes: 4 Sn 3 O 12 After the powder was ball-milled in a sand mill for 8 hours, powder D was obtained. 90 <100nm slurry, transfer the slurry to a stirrer, add citric acid to make the concentration of citric acid in the slurry 0.8mol / L, and stir at a speed of 80rpm for 5h, then add a binder and a plasticizer to the slurry and stir, and then spray granulate to obtain granulated powder.

[0094] In step S2:

[0095] The molding pressure of the mold is 140 MPa. After demolding, the blank is cold isostatically pressed at 180 MPa for 40 minutes to obtain a blank.

[0096] In step S3:

[0097] The sintering process includes: heating the green billet to 700°C at a rate of 1.5°C / min and keeping it warm for 4 hours, then heating it to 1360°C at a rate of 2°C / min, while introducing oxygen at a rate of 15L / min and keeping it warm for 4 hours. After the insulation is completed, keep it at 1200°C for 8 hours, and finally cool it to room temperature at a rate of 3°C / min.

[0098] Example 2 to Example 6

[0099] The difference from Example 1 is that the contents of metal indium and metal tin in the raw materials are different, and the maximum sintering temperature in step S3 is different. The details are shown in Table 1.

[0100] Table 1 Raw material composition and target maximum sintering temperature of comparative examples and examples

[0101]

[0102]

[0103] Comparative Example 1

[0104] The difference from Example 3 is that in Comparative Example 1, indium oxide and tin oxide are used as raw materials, which are mixed evenly and then kept warm in multiple temperature ranges at one time, and the subsequent sanding, organic acid activation, molding and sintering temperature regimes are the same as those in Example 3.

[0105] Comparative Example 2

[0106] The difference from Example 3 is that the precipitation method of Comparative Example 2 is: ammonia water is gradually dripped into the mixed solution of indium nitrate and tin nitrate, and no dispersant is added and ultrasound is turned on, and the other processes remain the same.

[0107] Comparative Example 3

[0108] The difference from Example 3 is that the comparative example 3 does not use organic acid to activate In 4 Sn 3 O 12 Powder, the rest of the process remains the same.

[0109] Test Case

[0110] The density, average resistivity and maximum resistivity difference rate of the target materials prepared in the examples and comparative examples were tested.

[0111] The density of the target material was tested by the Archimedes drainage method, and the surface resistivity of the target material was tested by a four-probe resistivity tester. Each target material had no less than 10 test areas, and the average value, i.e., the average resistivity, and the difference between the maximum and minimum resistivity values, i.e., the maximum resistivity difference rate, were taken. The results are shown in Table 2.

[0112] Table 2 Density and resistivity of examples and comparative examples

[0113]

[0114]

[0115] From the target material performance parameters of Examples 1-6 in Table 2, it can be seen that all the targets have high density (≥99.2%) and low resistivity (≤8×10 -4 Ω·cm), and the resistivity difference at different positions on the target surface is less than 8.0%, showing a high degree of uniformity.

[0116] Compared with Example 3, Comparative Examples 1 and 2 have the same chemical composition of the target materials, and the powder ball milling, granulation and sintering processes are completely consistent, but the prepared target materials are relatively low in density, higher in resistivity and poor in uniformity. This is mainly because Example 3 adopts co-precipitation mixing, and ammonia water is always in an excess state during the precipitation process. At the same time, the dispersant is added and ultrasound is turned on. The combined effect of the three makes the indium tin ions mixed more uniformly during the precipitation process, making the target sintering process more densified and the uniformity of different regions of the target better.

[0117] Comparative Example 3 Compared with Example 3, the chemical composition of the target is the same, and the powder ball milling, granulation and sintering processes are completely the same, but the density of the prepared target is much lower than that of Example 3. This is mainly because Example 3 uses organic acid to activate In 4 Sn 3 O 12 Powder, thereby reducing the sintering activation energy of the powder and preferably reducing the sintering temperature. Therefore, under the same sintering process, Example 3 has a higher density, and thus has a lower resistivity and better uniformity.

[0118] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. In4Sn3O 12 The method for preparing a target material is characterized in that: The following steps are involved: S1: Using metal indium and metal tin as raw materials, dissolving them by acid to obtain a mixed metal salt solution, dropping the mixed metal salt solution into ammonia water to precipitate indium hydroxide and tin hydroxide precipitates, drying the indium hydroxide and tin hydroxide precipitates to obtain a mixed powder and heating the mixture to obtain In4Sn3O 12 powder, the In4Sn3O 12 The powder is activated and granulated by organic acid to obtain granulated powder; S2: forming the granulated powder through a mold to obtain a green blank; S3: Sintering the green blank to obtain the In4Sn3O 12 Target material.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass fraction of indium in the metallic indium and metallic tin raw materials is 39.5% to 56.8%.

3. The preparation method according to claim 1, characterized in that: In step S1, the acid includes concentrated nitric acid or concentrated hydrochloric acid; and / or, the concentration of the concentrated nitric acid is 50% to 65%; and / or, the concentration of the concentrated hydrochloric acid is 20% to 38%.

4. The preparation method according to claim 1, characterized in that: In step S1, the concentration of the ammonia water is 20% to 28%; and / or the amount of the ammonia water used is 1.08 to 1.20 times the amount required for the total generation of metal salts from metal indium and metal tin.

5. The preparation method according to claim 1, characterized in that: Step S1 also includes adding 0.2wt% to 0.6wt% of polyvinyl pyrrolidone to the ammonia water to promote the reaction to be complete, and starting ultrasonic dispersion while forming indium hydroxide and tin hydroxide precipitates. After complete precipitation, the obtained indium hydroxide and tin hydroxide precipitates are centrifuged and washed, and then spray-dried to obtain a mixed powder.

6. The preparation method according to claim 1, characterized in that: In step S1, the temperature-raising reaction process includes: keeping the temperature at 500°C to 600°C for 2h to 8h, keeping the temperature at 1000°C to 1200°C for 3h to 8h, and keeping the temperature at 1300°C to 1500°C for 1h to 5h; and / or, in step S1, the In4Sn3O 12 The process of powder activation and granulation by organic acid includes: 12 After the powder is ball-milled in a sand mill for 6h to 10h, powder D is obtained. 90 <100nm slurry, transfer the slurry to a stirrer, add organic acid to make the acid concentration in the slurry 0.3mol / L~1.2mol / L, and stir at a speed of 50rpm~120rpm for 2h~8h, then add binder and plasticizer to the slurry and stir, then spray granulate to obtain granulated powder.

7. The preparation method according to claim 1, characterized in that: In step S2, the molding pressure of the mold is 100MPa-180MPa, and after demolding, cold isostatic pressing is performed at 150MPa-220MPa for 20min-60min to obtain a green blank.

8. The preparation method according to claim 1, characterized in that: The sintering process includes: heating the green blank to 600°C-800°C at a rate of 0.5-2°C / min and keeping the temperature for 2h-6h, then heating the green blank to 1300°C-1450°C at a rate of 1-3°C / min, introducing oxygen at a rate of 5L / min-30L / min, and keeping the temperature for 1h-5h, after the heat preservation is completed, keeping the temperature at 1150°C-1300°C for 5h-10h, and finally cooling the temperature to room temperature at a rate of 1°C / min-5°C / min.

9. In4Sn3O 12 The target material is characterized in that The method is prepared according to any one of claims 1 to 8.

10. In4Sn3O according to claim 9 12 The target material is characterized in that The In4Sn3O 12 The density of the target material is ≥99.2%, and the resistivity is ≤8×10 -4 Ω·cm.

Citation Information

Patent Citations

  • Preparation method of high-density low-indium-content ITO target material

    CN118084480A

  • Method for preparing indium tin oxide (ITO) target material with single-phase structure and high density

    CN101812665A

  • Gallium-molybdenum-codoped indium tin oxide ceramic target, gallium-molybdenum-codoped indium tin oxide transparent conductive film and preparation method

    CN102181826A

  • Preparation method of yttrium silicate ceramic powder

    CN104003699A

  • Preparation method of high-relative density and low-resistivity indium tin oxide target material

    CN105669186A